Harnessing personal smart tools for enhanced STEM education: exploring IoT integration - Yevhenii B. Shapovalov; Zhanna I. Bilyk; Stanislav A. Usenko; Viktor B. Shapovalov; Kateryna H. Postova; Sergey O. Zhadan; Pavlo D. Antonenko (Academy of Cognitive and Natural Sciences, 2023)
In the realm of STEM education, various computer-based methodologies have been employed to invigorate student motivation, personalize learning experiences, and elevate the overall quality of education. However, the integration of Internet of Things (IoT) and smart tools for measuring parameters during educational research processes has garnered insufficient attention thus far. This neglect becomes all the more pronounced in light of the burgeoning popularity of personal smartwatches and bands among individuals. In this study, we develop innovative techniques for incorporating personal smart tools into STEM classes and research endeavors. By employing the Colmi Land 1, Xiaomi Mi Band, Samsung Smart Fitness Band, and Xiaomi Mi Smart Scale as testbeds, we conduct a comprehensive evaluation using the As Is - To Be Business Process Model and Notation method. The findings substantiate that our proposed methods exhibit superior efficacy compared to conventional educational processes. Moreover, this paper represents a pioneering effort in describing and offering ready-to-use techniques for utilizing personalized smart tools to measure parameters during experiments within educational contexts.